2018
DOI: 10.1007/s40243-018-0117-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnetron sputtered TiN thin films toward enhanced performance supercapacitor electrodes

Abstract: Supercapacitors as a new type of energy storage devices bridging the gap between conventional capacitors and batteries have aroused widespread concern. Herein, binder-free titanium nitride (TiN) thin film electrodes for supercapacitors prepared by reactive magnetron sputtering technology are reported. The effect of N 2 content on the supercapacitor performance is evaluated. A highest specific capacitance of 27.3 mF cm −2 at a current density of 1.0 mA cm −2 , together with excellent cycling performance (98.2% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 40 publications
1
6
0
1
Order By: Relevance
“…In order to more fairly evaluate the electrochemical performance of the LITN SMFCs, a Ragone comparison plot (Figure 3f; Figure S17, Supporting Information) is provided, showing a comparison of LITN SMFCs and some recently reported state‐of‐the‐art electrochemical capacitors for the high‐frequency application purpose (TiN nanowire, [ 11 ] corn‐like TiN nanorod, [ 28 ] TiN nanosheet, [ 50 ] TiN film, [ 51 ] TiN/VG, [ 52 ] printed MXene [ 53 ] and CDC [ 54 ] ) in terms of power density and energy density. Nevertheless, factors such as voltage range, scanning speed, active material loading, and encapsulation volume can all affect the final performance characteristics in this plot.…”
Section: Resultsmentioning
confidence: 99%
“…In order to more fairly evaluate the electrochemical performance of the LITN SMFCs, a Ragone comparison plot (Figure 3f; Figure S17, Supporting Information) is provided, showing a comparison of LITN SMFCs and some recently reported state‐of‐the‐art electrochemical capacitors for the high‐frequency application purpose (TiN nanowire, [ 11 ] corn‐like TiN nanorod, [ 28 ] TiN nanosheet, [ 50 ] TiN film, [ 51 ] TiN/VG, [ 52 ] printed MXene [ 53 ] and CDC [ 54 ] ) in terms of power density and energy density. Nevertheless, factors such as voltage range, scanning speed, active material loading, and encapsulation volume can all affect the final performance characteristics in this plot.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of TiN nanostructures using other techniques such as the hydrothermal process and thermal decomposition involves the participation of other gases such as oxygen, ammonia, and the requirement of extremely high temperatures (~800 °C). Depositing TiN nanostructures directly onto the substrates helps in improving the electrochemical performance due to the absence of any binder and conducting agents [ 61 ]. Magnetron sputtering facilitates the fabrication of highly conformal and pure binder-free thin films of TiN directly onto the substrates.…”
Section: Synthesis Techniques For Nanostructured Titanium Nitridementioning
confidence: 99%
“…With new type of ESDs, excluding outdated tests applied on supercapacitors, batteries and now supercapbatteries how to evaluate their "viability" and "portability" growths as a concern. Twisting and extending tests are the most used approaches to validate to the stability of flexible thin and stretchable energy storage devices, respectively [19,20].…”
Section: Thin Film Energy Storagementioning
confidence: 99%
“…Zhoucheng Wang et al demonstrated CrN symmetric thin film supercapacitor with the help of magnetron sputtering unit, and the symmetric device exhibited excellent cycling stability [49]. Zhoucheng Wang et al studied binder-free titanium nitride thin film electrodes prepared by magnetron sputtering unit for supercapacitors [20]. From the literature magnetron sputtering technology is one of advanced coating system even if comparable lot advantages than thermal evaporation technique, and magnetron sputtering is situated promising tool for flexible thin film electrode fabrications.…”
Section: Magnetron Sputteringmentioning
confidence: 99%